Targeting the metabolism of leukemia stem cells as a novel therapeutic strategy - Neal M Davies; Emmanuel A Ho (BioExcel Publishing Ltd, 2013)
Summary: unraveling our understanding of cancer stem cells and their role in the development and progression of acute myeloid leukemia could lead to improved outcomes.